Film and domestic space architectures, representations, dispositif - Baschiera, Stefano 1977-; De Rosa, Miriam 1981- (Edinburgh University Press, 2020)
Drawing on a broad range of theoretical disciplines - and with case studies of directors such as Chantal Akerman, Agnès Varda, Claire Denis and Todd Haynes, Amos Gitai, Martin Ritt, John Ford, Ila Bêka and Louise Lemoine - this book goes beyond the representational approach to the analysis of domestic space in cinema, in order to look at it as a dispositif
Title from publisher's bibliographic system (viewed on 07 Oct 2020)
Keywords: Home in motion pictures; Domestic space in motion pictures